Existence of positive solutions for system of second order integro-diﬀerential equations with multi-point boundary conditions on time scales - Krishnaveni, V.; Sathiyanathan, K. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we have investigated the existence of positive solutions for system of nonlinear itegro-differential equations with multi(m)-point boundary conditions on time scales. Existence of positive solutions are established via Guo-Krasnosel’skii fixed point theorem for operators on a cone in a Banach space. An example is given to illustrate the effectiveness of our proposed result.